Implementation of the Duties of the Batu Bara Regency National Narcotics Agency (BNNK) Regarding Empowering the Community in Preventing Abuse and Illicit Trafficking of Narcotics from an Islamic Criminal Law Perspective - Sri Wahyu Ningsih; Zulkarnain (Journal Equity of Law and Governance, 2024)
Drug Abuse and Illicit Trafficking is a serious problem that has a wide impact on the health, security, and welfare of the community including in Batu Bara Regency. The Batu Bara Regency BNN is an institution that has a role in implementing its duties and authorities. This study is important to understand the extent to which the duties and functions of the Batu Bara Regency BNN are running effectively through community empowerment. Community empowerment in preventing drug abuse and illicit trafficking and drug precursors is a strategy that aims to increase the active role of the community in efforts to prevent and overcome narcotics problems. This research method is qualitative descriptive using primary data obtained through field studies and interviews. The results of this study are that the Batu Bara Regency BNN has implemented its duties and authorities well, and has maximized the target. This can be seen from the fact that throughout the existence of the BNN, the State's target for the Batu Bara Regency BNN has all been achieved and even exceeded. However, it would be even better if there was more support such as budget support, human resource support, involvement of the Batu Bara Regency government and the private sector to contribute to the prevention and illicit trafficking of narcotics. The View of Islamic Criminal Law on Narcotics and the Duties and Authorities of the National Narcotics Agency in Community Empowerment is that narcotics and the control of their abuse are in line with the principles of maintaining the welfare of the people (hifz al ummah) and protecting the five main objectives of sharia (maqasid al-shariah): religion, soul, mind, descendants, and property. In Islamic criminal law, narcotics are likened to khamr and there are no types or groups of narcotics. Sanctions for narcotics crimes in Islamic law, the perpetrator is sentenced to ta'zir. Based on Surah Al-Maidah verse 90, it is clear that the prohibition on drinking khamr, the nature of khamr is intoxicating, as well as drugs have the same nature as khamr, so the law is the same as khamr, namely haram.